Bessel Functions - 10.6 Recurrence Relations and Derivatives
Jump to navigation
Jump to search
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
10.6#E3X | \displaystyle\BesselJ{0}'@{z} = -\BesselJ{1}@{z} |
diff( BesselJ(0, z), z$(1) ) = - BesselJ(1, z) |
D[BesselJ[0, z], {z, 1}] == - BesselJ[1, z] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
10.6#E3X | \displaystyle\BesselY{0}'@{z} = -\BesselY{1}@{z} |
diff( BesselY(0, z), z$(1) ) = - BesselY(1, z) |
D[BesselY[0, z], {z, 1}] == - BesselY[1, z] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
10.6#E3Xa | \displaystyle\HankelH{1}{0}'@{z} = -\HankelH{1}{1}@{z} |
|
diff( HankelH1(0, z), z$(1) ) = - HankelH1(1, z) |
D[HankelH1[0, z], {z, 1}] == - HankelH1[1, z] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
10.6#E3Xa | \displaystyle\HankelH{2}{0}'@{z} = -\HankelH{2}{1}@{z} |
|
diff( HankelH2(0, z), z$(1) ) = - HankelH2(1, z) |
D[HankelH2[0, z], {z, 1}] == - HankelH2[1, z] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
10.6#Ex5 | f_{\nu-1}(z)+f_{\nu+1}(z) = (2\nu/\lambda)z^{-q}f_{\nu}(z) |
|
f[nu - 1](z)+ f[nu + 1](z) = (2*nu/lambda)*(z)^(- q)* f[nu](z) |
Subscript[f, \[Nu]- 1][z]+ Subscript[f, \[Nu]+ 1][z] == (2*\[Nu]/\[Lambda])*(z)^(- q)* Subscript[f, \[Nu]][z] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
10.6#Ex15 | p_{\nu+1}-p_{\nu-1} = -\frac{2\nu}{a}q_{\nu}-\frac{2\nu}{b}r_{\nu} |
|
p[nu + 1]- p[nu - 1] = -(2*nu)/(a)*q[nu]-(2*nu)/(b)*r[nu] |
Subscript[p, \[Nu]+ 1]- Subscript[p, \[Nu]- 1] == -Divide[2*\[Nu],a]*Subscript[q, \[Nu]]-Divide[2*\[Nu],b]*Subscript[r, \[Nu]] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
10.6#Ex16 | q_{\nu+1}+r_{\nu} = \frac{\nu}{a}p_{\nu}-\frac{\nu+1}{b}p_{\nu+1} |
|
q[nu + 1]+ r[nu] = (nu)/(a)*p[nu]-(nu + 1)/(b)*p[nu + 1] |
Subscript[q, \[Nu]+ 1]+ Subscript[r, \[Nu]] == Divide[\[Nu],a]*Subscript[p, \[Nu]]-Divide[\[Nu]+ 1,b]*Subscript[p, \[Nu]+ 1] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
10.6#Ex17 | r_{\nu+1}+q_{\nu} = \frac{\nu}{b}p_{\nu}-\frac{\nu+1}{a}p_{\nu+1} |
|
r[nu + 1]+ q[nu] = (nu)/(b)*p[nu]-(nu + 1)/(a)*p[nu + 1] |
Subscript[r, \[Nu]+ 1]+ Subscript[q, \[Nu]] == Divide[\[Nu],b]*Subscript[p, \[Nu]]-Divide[\[Nu]+ 1,a]*Subscript[p, \[Nu]+ 1] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
10.6#Ex18 | s_{\nu} = \tfrac{1}{2}p_{\nu+1}+\tfrac{1}{2}p_{\nu-1}-\frac{\nu^{2}}{ab}p_{\nu} |
(diff( BesselJ(nu, a), a$(1) )*diff( BesselY(nu, b), b$(1) )- diff( BesselJ(nu, b), b$(1) )*diff( BesselY(nu, a), a$(1) )) = (1)/(2)*p[nu + 1]+(1)/(2)*p[nu - 1]-((nu)^(2))/(a*b)*p[nu] |
(D[BesselJ[\[Nu], a], {a, 1}]*D[BesselY[\[Nu], b], {b, 1}]- D[BesselJ[\[Nu], b], {b, 1}]*D[BesselY[\[Nu], a], {a, 1}]) == Divide[1,2]*Subscript[p, \[Nu]+ 1]+Divide[1,2]*Subscript[p, \[Nu]- 1]-Divide[\[Nu]^(2),a*b]*Subscript[p, \[Nu]] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
10.6.E10 | p_{\nu}s_{\nu}-q_{\nu}r_{\nu} = 4/(\pi^{2}ab) |
p[nu]*(diff( BesselJ(nu, a), a$(1) )*diff( BesselY(nu, b), b$(1) )- diff( BesselJ(nu, b), b$(1) )*diff( BesselY(nu, a), a$(1) ))- q[nu]*r[nu] = 4/((Pi)^(2)* a*b) |
Subscript[p, \[Nu]]*(D[BesselJ[\[Nu], a], {a, 1}]*D[BesselY[\[Nu], b], {b, 1}]- D[BesselJ[\[Nu], b], {b, 1}]*D[BesselY[\[Nu], a], {a, 1}])- Subscript[q, \[Nu]]*Subscript[r, \[Nu]] == 4/((Pi)^(2)* a*b) |
Skipped - no semantic math | Skipped - no semantic math | - | - |